Preservation of alveolar ridge using graft material after tooth extraction: A clinical trial - Kunal Kumar; Revati Singh; Vishal Mugal; Nikhil Dhingra; Priyanka Priyadarshni; Subhash Bandgar (Wolters Kluwer Medknow Publications, 2021)
Background: The alveolar process is a tooth-dependent structure, and hence, removal of teeth results in the alteration of alveolar process. To alter bone remodeling after dental extraction, various techniques have been put forward for ridge preservation. Aim: The aim of this study is to evaluate and compare the changes of hard and soft tissues in postextraction socket after the application of bone graft material. Materials and Methods: Healthy patients of sample size of 40 were selected who underwent the extraction of anterior tooth irrespective of the arch, from premolar of one side to another, with the exception of incisors in mandible. Twenty patients were randomly selected as the control group and other 20 as the experimental group using an allograft bone material, i.e., beta-tricalcium phosphate to fill the socket. Cone-beam computed tomography (CBCT) was done as baseline preoperative and postoperative at 14 weeks after the extraction. CBCTs data help in recording linear and volumetric measurements which was performed by calibrated examiners to record all the measurements. After measurements, digital planning of dental implants was performed. Results: Forty participants were selected, in which 20 patients each were as the experimental and control groups. No significant difference was found at basal line at any of the cases. At follow-up of 14 weeks, statistical significance was seen in buccal and lingual plate height in the experimental group, and no significant difference was seen in the control group.(P = 0.023). Conclusions: This study clearly points out that an alveolar ridge preservation technique provides therapeutic benefit by limiting bone resorption in comparison to extraction alone.